Drama "Mazepa" by I. Karpenko-Karyi on the background of the literary and socio-political life of the XIXth century (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The article deals with the comparative analysis of drama I. Karpenko-Kary «Mazepa» with the poems by O. Pushkin «Poltava» and K. Ryleev «Wojnarowskiy». It is argued that using the plot of Pushkin's «Poltava», Ukrainian playwright wrote a new original work, which has created two images of the Central character (the image of Mazepa-man and the image of Mazepa-policy), which to some extent opposed to each other.
Keywords: Pushkin; «Poltava»; Ryleev; «Wojnarowskiy»; Mazepa; the freedom’s ideals